2021
DOI: 10.24136/oc.2021.021
|View full text |Cite
|
Sign up to set email alerts
|

Quo Vadis, earnings management? Analysis of manipulation determinants in Central European environment

Abstract: Research background: The paper investigates the earnings management phenomenon in the context of Central European countries, attempting to identify the factors and incentives that can influence earnings management behavior on a sample of 8,156 enterprises from Slovakia, the Czech Republic, Hungary, and Poland. Purpose of the article: The main purpose of the manuscript is to prove that there are significant differences in earnings management practices (measured by discretionary accruals) across the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 75 publications
0
30
0
Order By: Relevance
“…Since corporate governance and enterprise investment behavior will affect the financial status and operating results of enterprises to a great extent, more and more scholars pay attention to relevant research. Enterprise financialization is an important investment behavior of enterprises, and it is particularly important to study its influencing factors [26,27]. From the micro-level, Song and Lu [28] and Li et al [29] found that enterprises with high and low performance have a higher degree of financialization, while enterprises with medium performance have a lower trend of financialization.…”
Section: Influencing Factors Of Enterprise Financializationmentioning
confidence: 99%
“…Since corporate governance and enterprise investment behavior will affect the financial status and operating results of enterprises to a great extent, more and more scholars pay attention to relevant research. Enterprise financialization is an important investment behavior of enterprises, and it is particularly important to study its influencing factors [26,27]. From the micro-level, Song and Lu [28] and Li et al [29] found that enterprises with high and low performance have a higher degree of financialization, while enterprises with medium performance have a lower trend of financialization.…”
Section: Influencing Factors Of Enterprise Financializationmentioning
confidence: 99%
“…Every country has differences in earning which are cohered to different macroeconomic and microeconomic determinants (Valaskova, 2021). Time series predictions can be used for exchange rate analysis (Machova, Marecek, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of the macro-and microeconomic determinants working together we see in the major economies across the world. According to Valaskova (2021) paper factors such as behaviour of managers, comparing the influence of similar factors across countries detect the critical intentions management of earnings. Their own companies, and others, which are based there, influence every country.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While Kliestik et al [6], referring to Schipper (1989), have emphasized that "The importance of earnings management was underlined by Schipper (1989) whose research focused on three issues: defining the object of earnings management, exploring conditions giving rise to earnings management and designing of empirical tests". Valaskova et al [7] drawing on the work Bin et al (2018), maintain that earnings management is a sound and legal way of managing and reporting business activities aimed at achieving stable and predictable financial results.…”
Section: Introductionmentioning
confidence: 99%